Association between betel nut (Areca catechu L.) consumption and hemoglobin levels and mid-upper arm circumference in pregnant women in Jayapura Regency, Papua - Rante Allo Bela Sarni; Maharani Halim Annisaa (BIO Web of Conferences)
Anemia is a serious global public health problem that affects pregnant and postpartum women, where the number of red blood cells or hemoglobin concentration is lower than the normal levels. Betel nuts contain high levels of bioactive compounds including alkaloids and polyphenols which are believed to inhibit the absorption of nutrients including iron in the digestive tract. This research analyzes the correlation between betel nuts consumption, Hb levels, and MUAC. This research was conducted on 100 pregnant women using purposive sampling in three health center service areas within Jayapura Regency. Data on betel nut consumption was collected by questionnaire, Hb levels by Hemoglobinmeter, and MUAC by MUAC measuring tape. Data were analyzed using the Pearson correlation. This study's results show a significant negative association between the eating of betel nuts and hemoglobin levels (r=-0.359; p=0.001). Betel nut consumption is not significantly negatively correlated with MUAC (r=-0.022; p=0.830). It is recommended that pregnant women limit their consumption of betel nuts during pregnancy.